Loss-of-function mutation of NSD2 is associated with abnormal placentation accompanied by fetal growth retardation in mice. - Eriko Ohnishi; Shiori Kinoshita; Kazuhiko Nakabayashi; Kenichiro Hata; Tomoko Kawai (PLoS ONE, 2025)
Nuclear receptor-binding SET domain-containing 2 (NSD2) is the primary enzyme responsible for the dimethylation of histone H3 lysine 36 (H3K36me2), a marker associated with active gene transcription and intergenic DNA methylation. NSD2 is required for the normal development of humans and mice; however, its function during placentation remains unknown. Using genome editing techniques, we previously established two lines of Nsd2-mutant mice that showed growth retardation and neonatal lethality. Here, we further demonstrated that the loss-of-function mutation of NSD2 caused enlargement of the mouse placenta with morphological changes during late-gestation. Nsd2-mutant placentas were significantly heavier and showed thicker fetal layers with an expanded junctional zone and dilatated maternal blood sinuses in the labyrinth compared to their wild-type littermates. Abnormal placentation was accompanied by fetal growth defects, some with edema and one with a congenital cardiovascular anomaly, which may have partially affected neonatal survival. To our knowledge, this is the first study demonstrating the physiological and pathological functions of NSD2 during placentation.